Public Investment Projects in the Conditions of Changing Risk Factors - Krzysztof JAROSINSKI; Benedykt OPALKA (Communications of International Proceedings, 2021)
The purpose of the paper is to identify the conditions of financing public investments in the face of increased macroeconomic risk. Crisis phenomena and unpredictable changes in the economy increase the risk of implementing public investments. The concept of the article is closely related to the changes taking place in the public finance sector in the face of crisis phenomena. As part of the research, many new negative factors affecting public investment were observed, especially in view of the development of the Covid-19 pandemic. The instability of development processes resulted in a decline in GDP, an increase in inflation, an increase in the budget deficit and public debt. This leads to a change in the principles of financing and the effectiveness of public tasks. Paper is an attempt at a new approach to the implementation of public investment projects in conditions of increased risk, in particular macroeconomic risk. This leads to the necessity to conduct in-depth research on the effectiveness of public investments in conditions of significant changes in the main economic factors. This should lead to the reduction of the risk of unfavorable changes in projects and should be a new direction of research into public investment projects in a changing economic environment.
Keywords: Public Finance; Public Investments; Economy; Effectiveness.